Menstrual Hygiene Management: Linking with Education and Development. Issue 1 (June 2021) - Ganguli, Barna
Menstruation is a very normal physiological process for every female falling in the reproductive age-group, but still it is considered a taboo and a subject seldom openly discussed in most of the developing countries worldwide and India is no exception. Menstrual hygiene is still the most challenging issue because being a conservative topic, not much is spoken and discussed about it, and that is how the menstrual hygiene management (MHM) becomes an important task. As this is related to the well-being of half of the population, it becomes utmost important to address the problem. It is seen that education has a direct impact on understanding hygiene and hygiene has a direct role to play in development. Thus, states with good social and economic indicators are better performers of MHM. The present article tries to explore the connection of MHM with that of education and development. To make a comparative study and to establish this direct relationship of education and development, four states have been selected—Bihar and Jharkhand, from lower-income groups, and Kerala and Karnataka, from higher-income groups. The article also lays stress on the fact that optimizing menstrual hygiene interventions will require an integration of both knowledge and better living conditions alongside an augmentation of access to clean water, sanitation and hygiene facilities in addition to the availability of affordable hygienic sanitary products. Finally, the article also recommends the government to enhance the coverage and utilization of public fund on the issue so that every woman between 15 and 49 years gets the advantage of MHM irrespective of her social strata.